Depression of Mitochondrial Function in the Rat Skeletal Muscle Model of Myofascial Pain Syndrome Is Through Down-Regulation of the AMPK-PGC-1α-SIRT3 Axis - Ye, Le (J Pain Res, 2020)
PURPOSE: The causative mechanisms triggering myofascial pain syndrome (MPS) are still in debate. It is becoming evident that mitochondrial dysfunction may regulate pathways controlling MPS. The aim of this study was to investigate whether AMPK-PGC-1α-SIRT3 axis is associated with depression of mitochondrial function in the rat MPS model. METHODS: A total of 32 Sprague–Dawley rats were randomly divided into control group and experimental group. The expression level of mRNA and protein of gastrocnemius medialis (GM) was analyzed by Western blot and RT-PCR. The histopathological findings were investigated through electron microscopes in GM of all groups. RESULTS: Our results showed that MPS induces continuous depression of mitochondrial biogenesis and function via down-regulation of PGC-1α-SIRT3 axis accompanying with ATP fuel crisis as compared to control group. However, the expression level of SIRT3 mRNA did not change. Additionally, a correlated reduction of the mRNA and protein expression level of NRF-1 and TFAM, known as the downstream target of PGC-1α, suggesting further transcription of nuclear genes encoding mitochondria functional proteins for promoting mitochondria proliferation, oxidative phosphorylation and energy production is continuously depressed. Furthermore, phosphorylation extent of AMPK is also declined following MPS, and it is negatively correlated with reduction of ATP generation, suggesting that the complex network involves different inhibition in transcription, post-translational modification and a plethora of other effectors that mediate the inhibition roles. CONCLUSION: We here suggested that the down-regulation in AMPK-PGC-1α-SIRT3 axis network may be the basis for the association between mitochondrial dysfunction and MPS, where a vicious circle further aggravates the disease symptoms with ongoing ATP energy crisis.